(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background: This research intended to assess the impact of various taurine dosages on angiogenesis and their effect on some hematological and biochemical traits (Hemoglobin (Hb), packed cell volum PCV, cholesterol, triglyceride ,glutathion GSH, malondialdehyde MDA, body weight of animal after and before experiments, and hepatocyte tissues. in rats males exposed to Taurine (500,1000,1500,2000) mg for months. Material and Method: Six groups of eight rats each were created from the rats. Six groups of eight rats each were created from the rats. receiving different doses of taurine. Result: results revealed a significant increase for (Hb, PCV, GSH, body weight before experiment) while a significant decrease to (TG, MDA, Cholesterol, body weight after experiment), and many histological changes including congestion of sinusoidal and central vein, infiltration of inflammation cell around central vein and sever vacuolation of hepatocyte. Conclusion: High doses of taurine affect angiogenesis in hepatic tissue and stimulate hematological and biochemical responses.